Defining visual illusions in Parkinson's disease: Kinetopsia and object misidentification illusions. (October 2018) - Nishio, Yoshiyuki; Yokoi, Kayoko; Hirayama, Kazumi; Ishioka, Toshiyuki; Hosokai, Yoshiyuki; Gang, Miyeong; Uchiyama, Makoto; Baba, Toru; Suzuki, Kyoko; Takeda, Atsushi; Mori, Etsuro
Abstract: Objective: To identify the phenomenological features and neural correlates of visual illusions in Parkinson's disease (PD). Methods: Ninety-three patients with PD were assessed via questionnaires regarding visual illusions and behavioral symptoms, and neuropsychological tests, motor assessments and 18-F fluorodeoxyglucose-positron emission tomography (FDG-PET) were performed. The relationship between visual illusions or hallucinations and regional cerebral glucose metabolism was investigated using partial least squares (PLS) correlation and conventional mass-univariate analyses. Results: Kinetopsia, in which stationary objects are perceived as being in motion, and object misidentification illusions, in which objects are misperceived as different objects, were the most common types of visual illusions. Kinetopsia and object misidentification illusions were identified in 24 patients (25.8%) and 17 patients (18.3%), respectively. Eleven patients with kinetopsia and 9 patients with object misidentification illusions had visual hallucinations. Kinetopsia and visual hallucinations were associated with hypometabolism in the temporo-parietal cortices, whereas object misidentification illusions were associated with hypometabolism in the early visual cortex, as well as the temporo-parietal cortices. Conclusions: Our findings suggest that kinetopsia and object misidentification illusions are the most common types of visual illusions in PD. Despite the phenomenological diversity of visual illusions and hallucinations in PD, all of these symptoms are associated with dysfunction of the temporo-parietal cortices, which support visual spatial processing, rather than dysfunction of the ventral temporo-occipital cortices, which supports visual object recognition. Highlights: Kinetopsia is the most common type of visual illusions (VIs) in PD. Object misidentification illusions are the second most common type of VIs. Kinetopsia correlates with temporo-parietal hypometabolism. Neural correlates of kinetopsia and visual hallucinations overlap.